Savor the flavor: A randomized double‐blind study assessing taste‐enhanced placebo analgesia in healthy volunteers - Matthias Zunhammer; Gerrit Goltz; Maximilian Schweifel; Boris A. Stuck; Ulrike Bingel (Clinical and Translational Science, 2022)
Abstract Placebo effects substantially contribute to analgesic treatment outcomes and might be leveraged to enhance gold‐standard treatments. The taste of oral medications has been proposed to boost placebo effects. Here, we aimed at estimating how far the taste of an oral medication enhances placebo analgesia. We conducted a randomized, double‐blind, between‐group, single‐visit study, with pre‐treatment baseline. Over the course of three substudies, 318 healthy volunteers (297 included) were tested in a clinical trial setting. Participants were subjected to experimental tonic cold water pain (cold pressor test) before and after receiving taste‐neutral (water), or bitter (quinine), or sweet (saccharin), or no placebo drops. Pre‐ versus post‐treatment changes in area under the pain rating curve, the main outcome, indicated that placebo treatment showed a small analgesic effect versus no treatment. Added taste induced placebo enhancement in the very small effect size range, but accounted for a substantial portion of the overall placebo effect. No noteworthy advantage of sweet over bitter placebo was observed. An exploration of heart rate (HR) recordings indicated that placebo treatments were associated with an increase in peak HR‐response to cold water, but these were not associated with placebo analgesia at an individual level. Placebo treatments were associated with minimal side effects. These results indicate that added taste may be an easy‐to‐implement, cost‐effective, and safe way to optimize treatment outcomes and that taste‐neutral preparations may reduce placebo‐related outcome variance in clinical trials. Further studies are needed to test if these findings can be translated into clinical scenarios.